PENGARUH PEMBERIAN BERBAGAI JENIS BOKASHI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays Saccarata) - Usman Made, Imam Wahyudi, Siska Sari Mulyanti (AGROTEKBIS, 2015)
This study aims to determine the influence of some kind of Bokashi on the growth and yield of sweet corn. This research was conducted in the village of Sidera, District of Biromaru, Sigi, Central Sulawesi Province. Analysis of the soil, and Bokashi were conducted in the Laboratory of Soil Science, Faculty of Agriculture, University of Tadulako, Palu. This study used a randomized block design with 7 treatments that werecontrol, Bokashi of gamal 15 t ha-1, Bokashi of johar15 t ha-1, Bokashi of geanust leaf peanuts 15 t ha-1, Bokashi of chicken manure 15 t ha-1, Bokashi goat manure 15 t ha-1, Bokashi of cow manure 15 t ha-1. Each treatment was repeated 3 times so that there are 21 units experiments.Variabel observations were: plant high, stemdiameter ,total leaves , day of flower ins, cob length, diameter cob and sweet corn production (tons ha-1). Data were analyzed using ANOVA test if there are significant then tested further by using advanced test Honestly Significant Difference 5% (HSD 5%). The results showed that the granting of various types of Bokashi provide a significant influence on the growth and yield of sweet corn. Giving Bokashi Johar leaves give better results on the growth of sweet corn plants, while granting Bokashi Gamal leaves give better results against the results of sweet corn production.